Exploring the Realm of Arts and Theatre-Centric Approaches to Enhance Youth Mental Health and Well-being: An Explorative Scoping Review - Rajendran, Karthikeyan Pandiyambakkam; Victory R., Helen; Kalaveena V. S., Kalaveena V. S.; Thiruthuvarani S., Sangeetha; Ahmed, Thariq Akthar; Ramakrishnan P., Ramakrishnan P.; Raghavan D., Vijaya; Rangaswamy, Thara (Unisia, 2024)
In this world of uncertainties and challenges, mental well-being of youth is crucial. Experiential arts and theatre-based techniques have enormous potential to improve mental health and have profound therapeutic benefits. To explore and evaluate the impact and efficacy of various art and theatre-based interventions used solely to promote young people's positive mental health and well-being. Peer-reviewed reports published between 2002 and 2022, identified from databases such as PubMed, Ovid, Google Scholar, and ERIC, were used to collate and gather ideas on arts and theatre-based interventions for positive mental health and well-being in young people. From the 623 identified reports, a total of nine studies were identified. Arts-based interventions implemented in schools, community centers, and healthcare settings showed promising results in the mental well-being of young people. The outcomes evaluated were alleviation of symptoms, better emotional well-being, self-expression, improved self-esteem, and coping abilities. The findings of this scoping review suggest that art and theatre-based interventions can potentially improve young people's mental health. The wide range of interventions and results explores these techniques, the domains targeted, and their adaptability and efficacy suggest that they are far better than the other approaches.